Age-Related Trends in Body Composition among Women Aged 20–80 Years: A Cross-Sectional Study - Nirmala Rathnayake; Hasanga Rathnayake; Sarath Lekamwasam (Journal of Obesity)
The determinants of body composition are likely to vary geographically due to the diversity of genetic and environmental factors between populations. Age-related trends in body composition in a population help understanding the health issues that are linked with different body compartments. In general, such studies are scarce in the South Asian region and this cross-sectional study examined the age-related trends in body composition in a selected group of healthy women aged 20–80 years in Sri Lanka. The study included randomly selected 784 healthy women aged 20–80 years from the Southern province, Sri Lanka. Women were divided into five age groups: 20–29 years (n = 79), 30–39 years (n = 144), 40–49 years (n = 185), 50–59 years (n = 281), and ≥60 years (n = 85). Total body bone mineral density (TBBMD, g/cm2), total body bone mineral content (TBBMC, g), total body fat mass (TBFM, kg), and total body lean mass (TBLM, kg) were measured with central-type dual-energy X-ray absorptiometry (DXA). Multivariate analysis of variance with Bonferroni post hoc test was performed. The age-related trends of TBBMD and TBBMC were similar with a peak in 40–49-year age group. Between 50 and 59 and ≥60 age categories, TBBMD and TBBMC showed a rapid decline: 16% and 23%, respectively. The rate of TBBMD decline was 0.008 g/cm2 per year after 50 years. TBFM increased by 14% between age categories 20–29 and 40–49 years and remained unchanged after 49 years. TBLM increased by 15% between age groups 20–29 and 40–49 years and then decreased by 13% between age categories 50–59 and ≥60 years. Of the 13% decrease in TBLM after 50 years, 9% loss occurred after 59 years. The trends observed help to understand the occurrence of diseases linked with body composition.